Analysis Of Factors Affecting The Quality Of Financial Reports Of The Palopo City Government - Rahmadani, Anindya; A. Dahri Adi Patra Ls; Sari, Nispa (LP2M IAIN Palopo, 2025)
The quality of local government financial reports is a key indicator in measuring the accountability and transparency of public financial management. This study aims to analyze the factors influencing the quality of Palopo City Government's financial reports, focusing on three main variables: human resource competency, information technology utilization, and internal control systems. The research method used is a quantitative approach with data collection through questionnaires distributed to employees involved in the preparation of financial reports in Palopo City Government. The results show that human resource competency has a significant influence on the quality of financial reports, where employees with a good understanding of accounting standards and adequate training tend to produce more accurate and transparent reports. In addition, the use of information technology also contributes positively to increasing the efficiency and effectiveness of financial report preparation by reducing manual errors and accelerating data processing. Another influential factor is a strong internal control system, which helps ensure compliance with regulations and prevents irregularities in financial management. Therefore, this study provides recommendations for the Palopo City Government to improve employee competency through continuous training, strengthen the implementation of information technology in the financial system, and improve the internal control system to improve the quality of more accountable and transparent financial reports.